Equity or tradition?: Community women’s political participation in prior consultation processes - Potesta Cortez, Alexia (2020)
The purpose of this essay is to review the normative references of the prior consultation process, highlight the legal gaps in the the gender approach application and analyze the factors that weaken the participation of peruvian community women in the process. The political situation of community women will be addressed qualitatively and the obstacles to their participation in the public sphere will be described through the review of legal references and academic research, . These notions reflect the need for a government statutes and regulations renewal, and the design of intercultural methodologies that guarantee parity in the processes. Finally, the article questions whether prior consultation, in the practice, contributes to reinforcing customary power and gender structures and, in what extent its legal references discourage the participation of community women.